Triangle Points and the Upper Mississippians: Oneota and Fort Ancient Typologies - (:unkn) unknown (My University, 2020)
The Fort Ancient and Oneota cultures have long been noted for their similarities. It is my intent to analyze the stone tools from two sites crossculturally to determine whether these similarities exist beyond the superficial and visual and extend to the reality of daily life, economic, social, or subsistence practices. Such an analysis reveals a methodological divide between regional archaeologists and their attempts to interpret ostensibly identical data, which has altered how each culture is interpreted and impacts the ability to compare the cultures. This paper will examine the regional data presentations and the impact of these differences upon the current state of the archaeological record.